Speech resonance in orthognathic surgery in subjects with cleft lip and palate - Niemeyer, Trixy Cristina (2005)
The main purpose of this study was to investigate the impact of maxillary advancement on speech resonance in subjects with cleft lip and palate. The study sample was composed of 42 subjects aged 16 to 41 years old with operated cleft palate ± lip submitted to maxillary advancement. Resonance was evaluated before and 3 to 12 months after surgery by perceptual analysis and graduated from absent to severe. It was observed that 47.5% of the subjects presented impairment of resonance after orthognathic surgery, with a confidence interval (at 95%) from 31.5% to 63.9%. These results suggest that orthognathic surgery in individuals with cleft palate may interfere in resonance, causing, or increasing the degree of hypernasality. Therefore, this highlights the importance of the orientation about the risks and benefits of maxillary advancement surgery and follow-up of these patients.